2019
DOI: 10.1094/phyto-06-18-0199-le
|View full text |Cite
|
Sign up to set email alerts
|

Cautionary Notes on Use of the MoT3 Diagnostic Assay for Magnaporthe oryzae Wheat and Rice Blast Isolates

Abstract: The blast fungus Magnaporthe oryzae is comprised of lineages that exhibit varying degrees of specificity on about 50 grass hosts, including rice, wheat, and barley. Reliable diagnostic tools are essential given that the pathogen has a propensity to jump to new hosts and spread to new geographic regions. Of particular concern is wheat blast, which has suddenly appeared in Bangladesh in 2016 before spreading to neighboring India. In these Asian countries, wheat blast strains are now co-occurring with the destruc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Since M. oryzae is a species complex and disease symptom of wheat blast is always confused with that caused by Fusarium head blight, it is therefore important to diagnose the disease accurately to apply suitable control measure timely. Interestingly, our previous results using M. oryzae isolates from rice and wheat blast showed that MoT3 primers were not specific for MoT isolates under certain conditions (Gupta et al 2019). This result was contradictory with that obtained by Pieck et al (2017).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Since M. oryzae is a species complex and disease symptom of wheat blast is always confused with that caused by Fusarium head blight, it is therefore important to diagnose the disease accurately to apply suitable control measure timely. Interestingly, our previous results using M. oryzae isolates from rice and wheat blast showed that MoT3 primers were not specific for MoT isolates under certain conditions (Gupta et al 2019). This result was contradictory with that obtained by Pieck et al (2017).…”
Section: Discussionmentioning
confidence: 76%
“…In this study, pot2-transposon specific primers were used to amplify Pot2 region that is thought to be present in isolates of M. oryzae and M. grisea from different hosts (Harmon et al 2003). A recently developed primer by Pieck et al (2017) named MoT3 was also used, which is unique for identification of isolates of M. oryzae Triticum pathotype when used under stringent conditions (Gupta et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This method may be useful in detecting trapped MoT spores from the aerosol samples and for the prediction of epidemics along the year. However, Gupta et al (2019) published a result contradictory to the previous result of Pieck et al (2017) as they observed that under certain conditions, MoT3 primers also amplify both rice and wheat blast isolates. The assay is based on primers matching the WB12 sequence corresponding to a fragment of the M. oryzae MGG_02337 gene that is annotated as a short chain dehydrogenase and is present in both rice and wheat infecting M oryzae isolates.…”
Section: Introductionmentioning
confidence: 69%
“…Although some diagnostic protocols have been developed for the wheat blast, they are not highly convenient and unequivocally reliable (Pieck et al 2017;Gupta et al 2019). Therefore, a more convenient, rapid and costeffective diagnostic tool needs to be developed for surveillance and monitoring of this wheat pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of wheat for food security in South Asia and India in particular, the present study, therefore, calls for concerted action from the national governments in South Asia and international stakeholders. Until now, there is no specific molecular diagnostic tool for the determination of wheat blast [63] in suspected seeds, alternative hosts and symptomless plants. There is an urgent need to develop a convenient diagnostic tool for wheat blast to support surveillance and to invest in disease epidemiology and forecasting research.…”
Section: Materials and Methods: Context And Ex-ante Estimation Proceduresmentioning
confidence: 99%